2018
DOI: 10.1039/c7nh00187h
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale membrane architecture of healthy and pathological red blood cells

Abstract: Red blood cells present a complex cell plasma membrane architecture with submicrometric organization leading to nanomechanical heterogeneities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 57 publications
4
40
0
Order By: Relevance
“…5c, e), which is in the range of values reported for E. coli (0.04 N m −1 ) 25,26 and for the two other Gram-negative bacteria Shewanella putrefaciens (0.02-0.05 N m −1 ) 19 and Pseudomonas aeruginosa (0.02 N m −1 ) 27 . We note that similar trends were obtained using the FV and QI modes, the later yielding larger values, which we believe results from the much higher speed of QI 28 .…”
Section: Resultssupporting
confidence: 81%
“…5c, e), which is in the range of values reported for E. coli (0.04 N m −1 ) 25,26 and for the two other Gram-negative bacteria Shewanella putrefaciens (0.02-0.05 N m −1 ) 19 and Pseudomonas aeruginosa (0.02 N m −1 ) 27 . We note that similar trends were obtained using the FV and QI modes, the later yielding larger values, which we believe results from the much higher speed of QI 28 .…”
Section: Resultssupporting
confidence: 81%
“…We can therefore not exclude the possibility that the Chol-enriched domain population that was not revealed by Laurdan exhibits a higher order than the bulk. Accordingly, high spatial resolution atomic force microscopy of the RBC membrane allowed us to reveal lipid domains correlated with both local minima and maxima areas in the Young's modulus maps [33]. This suggests that the RBC membrane is composed of lipid domains exhibiting differential local mechanical properties, which could depend on the specific lipid domain composition and on their differential association to membrane and cytoskeletal proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, by mimicking RBC membrane vesiculation upon aging by storage at 4°C, we showed that both lipid domains represent specific sites for membrane vesiculation upon aging [31]. Fourth, we recently showed by high spatial resolution atomic force microscopy that the RBC membrane is composed of lipid domains exhibiting differential local mechanical properties, which could depend on their differential association to the cytoskeleton and on their specific lipid composition [33]. However, atomic force microscopy does not allow to determine the lipid composition of the domains nor to evaluate how their mechanical properties are modulated upon RBC deformation.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we also used atomic force microscopy, a high-resolution technique applicable to cells in their native state (i.e. without labeling), to study the biophysical properties of these domains [28]. The chol-and SM-enriched domains differ in abundance and biophysical properties (i.e.…”
Section: Introductionmentioning
confidence: 99%